The impact of green banking activities on banks' green financing and environmental performance - Daniel Cardona Valencia; Carola Calabuig-Tormo (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2023)
This study aims to empirically assess the impact of green banking activities on banks' green financing and environmental performance. Likewise, it seeks to identify the mediating effect of green financing on the relationship between banks' environmental performance and green banking activities. It also examines the trends and challenges on the topic. Structural equation modeling was used to evaluate the relationship between the variables identified from primary data collected through a structured questionnaire administered to 321 Colombian bankers, who were selected using convenience sampling. According to the results, green banking activities have a positive impact on banks' environmental performance, and banks' sources of green financing significantly influence their environmental performance. Notwithstanding, green banking is regarded as a promising strategy for banks because it enhances their competitiveness and reputation, helps them reduce their carbon footprint and costs in the long term, and enables them to be included in sustainability indexes.
Keywords: F65; Q01; Q56; 330; Green banking; Sustainability; Green finance; Financial inclusion; Green financing; Environmental performance